In Vitro Study: Antimalarial Activity of Rivet Sea Cucumber Extract (Holothuria atra) With Ethyl Acetate Solvent Against Plasmodium falciparum : none - Prawesty Diah Utami; Zuhro Putri Febrianti Febrianti (Warmadewa University, 2022)
Abstract Indonesia is experiencing a decreased cure rate of malaria caused by the species Plasmodium falciparum. Alternative medicine, in this case, uses marine biota, namely lollyfish (Holothuria atra), which has a lot of active compound content; the purpose uses the biota because many reports that there is a failure of malaria treatment therapy due to Artemisinin-based Combination Therapy (ACT) resistance. The purpose of this study was to find out the antimalarial activity of Holothuria atra extract with ethyl acetate solvent at dose 0.01; 0.1; 1; 10; and 100 Ug/ml against Plasmodium falciparum in vitro. Extract lollyfish using the maceration method. The lollyfish powder will be dissolved with ethyl acetate solvent for 24 hours. Antimalarial activity testing is measured through 4 parameters, namely the measurement of parasitemia rates, % parasite growth, % inhibitory rate, and IC50. Antimalarial activity with ethyl acetate solvent belongs to a very active category with an IC50 value of 1.52 Âµg/mL. These results can kill the P. falciparum parasite with a percentage that reaches 0%. A decrease in the percentage of growth occurs when the dose given is too low so that the parasite can grow and survive. The result of higher concentrations of extracts will have a higher percentage of resistance to the growth of parasites. The potential for antimalarial activity in lollyfish extract is influenced by the presence of active content such as alkaloids, flavonoids, catechins, and pyrogallol owned by marine biota animals. This study suggests that lollyfish (H. atra) can be developed as an alternative treatment for malaria. Keywords: Holothuria atra, antimalarial, Plasmodium falciparum, in vitro